Effect of Marketing Mix on Satisfaction of Customers Indosat - Galih Wisnu Wardhana (Journal of Indonesian Science Economic Research, 2020)
The purpose of this study is to analyze the effect of the marketing mix consisting of products, prices, promotions, and location on the Consumer Satisfaction of Indosat Card Users. The population in this study were students at STIE AUB Surakarta, taking incidental sampling techniques obtained a sample of 200 respondents. The results of the multiple linear regression equation show that Y = -2,003+ 0,143 X1 + 0,279 X2 + 0,255 X3 + 0,456 X4, meaning that product, price, promotion, and location have a positive effect on customer satisfaction. The regression coefficient value for Access variable has the biggest regression coefficient among other variables, which means that Access variable is the dominant variable in this study. F test results show that together the product, price, promotion, and location variables affect customer satisfaction. R2 test results (coefficient of determination) note that the product, price, promotion, and location variables are able to explain 82.6% of the Indosat Card customer satisfaction variables, while the remaining 17.4% are explained by other variables such as company image, trustworthiness, and service quality.